2021
DOI: 10.3390/jcm10061155
|View full text |Cite
|
Sign up to set email alerts
|

Indication of Liver Transplantation for Hepatocellular Carcinoma Should Be Reconsidered in Case of Microvascular Invasion and Multilocular Tumor Occurrence

Abstract: Liver transplantation (LT) is routinely performed for hepatocellular carcinoma (HCC) in cirrhosis without major vascular invasion. Although the adverse influence of microvascular invasion is recognized, its occurrence does not contraindicate LT. We retrospectively analyzed in our LT cohort the significance of microvascular invasion on survival and demonstrate bridging procedures. At our hospital, 346 patients were diagnosed with HCC, 171 patients were evaluated for LT, and 153 were listed at Eurotransplant dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…( 32 ) also confirmed that p-TACE was an independent protective factor in the subgroup of tumor ≤ 5 cm but not in the subgroup of tumor > 5. At present, the research suggested that MVI after resection is not a contraindication for liver transplantation (LT) and demonstrated that LT should be reconsidered in case of MVI and multilocular tumor occurrence ( 33 ). However, further studies with improved design are needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…( 32 ) also confirmed that p-TACE was an independent protective factor in the subgroup of tumor ≤ 5 cm but not in the subgroup of tumor > 5. At present, the research suggested that MVI after resection is not a contraindication for liver transplantation (LT) and demonstrated that LT should be reconsidered in case of MVI and multilocular tumor occurrence ( 33 ). However, further studies with improved design are needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, tumor biology seems to be decisive for prognosis after LT 13 . In addition to grading and microvascular infiltration 14 , the response to locoregional therapy is an important prognostic predictor 13 . Furthermore, the identification of patients with an increased risk of recurrence after resection is also important, because nearly half of the patients with early -stage HCC experience recurrence after resection mainly within 2 years after surgery 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The keyword generator is designed to annotate DICOM and PNG data based on Flask: 1) For DICOM images, the ingest component extracts and indexes the standard DICOM header. Over 100 DICOM images of 7 anonymized test patients in the research project TOMAS [3] are extracted and indexed in ES. ; 2) Alternatively, for unannotated PNG images, the component uses a "Deep Learning (DL) keyword generator" to generate appropriate instance-level image captions.…”
Section: Methodsmentioning
confidence: 99%